Analysis of main ergometric parameters of elite kayak athletes specialized in different distance events - Ieremenko, N.; Shynkaruk, O.; Moseychuk, Y.; Moroz, O.; Ivashchenko, O.; Yarmak, O.; Andrieieva, O.; Galan, Y. (SportMont, 2021)
The purpose of the study was to determine the level of the general functional potential of the body of elite kayak rowers for its subsequent effective realization under conditions of special training and competitive loads. The study involved 38 elite athletes, who had been the members of the Ukrainian national kayaking team. This article presents the results of the assessment of the functional state of elite athletes specialized in kayaking and canoeing. It was determined that athletes at a race distance of 1000 m under conditions of work at maximum aerobic capacity had the highest level of the power of the respiratory system (in terms of the level of pulmonary ventilation). The lowest level of the power of the respiratory system and a less eco- nomical type of breathing were observed in rowing athletes at a race distance of 200 m. Under conditions of maximum-intensity physical load with the engagement of the anaerobic glycolytic and aerobic systems to energy supply, which simulated the conditions of 500 m and 1000 m aces in kayaking, significant differences (p<0.05) were found in the maximum level of aerobic capacity and relative contributions of the anaerobic and aerobic metabolism in the overall energy production. The results of our study indicate that the level of general (basic) functional (aerobic and anaerobic potential of the body of elite rowing athletes is important for its subsequent realization.